Islamic Perspective: Communication in Overcoming Family Conflict to Build Harmony - Erny Fitroh Nabila Muwafiqi; Elok Halimatus Sa’diyah (STIT Attaqwa, 2023)
The object of this research is to overcome family problems with communication to achieve a harmonious family. The writing of this article was inspired by the Islamic religion which originates from the Koran. Many verses in the Qur'an describe the process of communication. The first time dialogue occurred between God, angels, and humans. This dialogue illustrates that humans have the potential for communication which is gifted by God. This potential is contained in QS. Al-Baqarah: 31-33. The author concludes that humans are social creatures who cannot be separated from social activities, one of which is interaction with family members. Family members need communication to create family harmony. Communication that occurs in the family can provide something good if you can manage the communication process. But it can also create misunderstandings. It is hoped that communication within the family can resolve problems that occur by discussing them together. The communication process is used to create and reach agreement on a solution. One form of communication that makes a family harmonious is saying the word